Strategi Branding Halal UMKM Kuliner Dan Dampaknya Terhadap Keputusan Pembelian Konsumen Muslim - Maryam Aqilah Kardi; Farras Jundi Al Kautsar (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
ABSTRACT Halal branding becomes an important strategy for culinary MSMEs in Indonesia as Muslim consumer awareness of halal products continues to increase. This study aims to analyze how halal branding strategies are implemented in culinary MSMEs and how these strategies influence Muslim consumers’ purchasing decisions. This research uses a qualitative method with a case study design by selecting one culinary MSME that applies halal-based branding. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using Miles and Huberman’s model through the stages of information simplification, presentation of findings, and conclusion drawing. The results show that halal branding strategies, such as halal identity, communication transparency, promotion, and halal customer experience, positively influence consumer trust and encourage purchasing decisions. This study contributes by providing in-depth insights into halal branding practices in MSMEs, a topic less explored compared to large-scale food industries. Keywords: halal branding; culinary MSMEs; Muslim consumers; purchasing decision.